Lower common pathway location detected by cryoablation of atrioventricular nodal reentrant tachycardia of the common variety - Kaoru Okishige; Takatoshi Shigeta; Rena A. Nakamura; Tatsuhiko Hirao; Hiroshi Yoshida; Yasuteru Yamauchi (Clinical Case Reports, 2019)
Abstract As different from radiofrequency current energy, cryofreezing energy is able to provide reversible effects on cardiac tissue, called “cryomapping,” which enables us to predict the effects of a subsequent application of ablative energy. Cryomapping is able to delineate the anatomical location of the lower common pathway of atrioventricular nodal reentrant tachycardia.